Pengaruh Pemberian Ekstrak Daun Tembelekan (Lantana camara L.) Terhadap Pertumbuhan Gulma Sintrong (Crassocephalum crepidioides) - Jumiati Jumiati; Nurlia Nurlia (Media Agribisnis, 2023)
Tembelekan is one type of dicotyledonous plant from the family Verbenaceae. This plant has the ability to invade the area where it grows because it has secondary compounds that can interfere with the presence of other plants around it. The purpose of this study was to see the effect of tembelekan leaf extract on the growth of sintrong weeds. This study used the Complete Randomized Design (RAL) method with 6 (six) concentration levels 0%, 15%, 30%, 45% and 60% with each test consisting of 5 (five) tests. The observed data were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level. The difference between treatments was further tested using Duncan's Multiple Range Test (DMRT) at Î±= 0.05 using SPSS 23 software. The result of the research showed a very significant inhibition of the germination of sintrong weeds. Sintrong weed seeds did not germinate either treated with distilled water extract or ethanol extract of tembelekan leaves.